Optimizing pedigrees: Using a biasing system to determine likely inheritance systems - Ang, Justin (PeerJ Preprints, 2017)
Pedigrees, though straightforward and versatile, lack the ability to tell us information about many individuals. Though numerical systems have been developed, there has yet to be a system that tells us the probabilities of a tree following certain inheritance systems. My system intends to do that by creating a flexible numerical system, which can then be tested for variance. My system attempts to adapt inheritance system to known pedigree data. Then, it calculates where the calculated values differ from the known pedigree data. It aggregates these values, then uses them in a chi-squared analysis in order to determine how likely the inheritance system is to match the pedigree. This is done for many different systems, until we have a good idea of what system the pedigree matches or doesn't match.
Keywords: Pedigree; Chi-Squared; Biasing System; Inheritance; Statistics; Algorithm